The representation of a woman judge in the Italian press. The case of Ilda Boccassini - Verza, Sofia; Bonerba, Giuseppina (Ámbitos. Revista Internacional de Comunicación, 2023)
Various studies have highlighted how the media representation of the judiciary in Italy has shifted from the exaltation of judges who worked on cases of relevant public interest (for example, the Tangentopoli case) to a growing conflict between the judicial body and the political elite. This work focuses on the representation of the judge Ilda Boccassini by four Italian national newspapers during 2011, the year in which she conducted the investigations relating to the «Ruby trial», against the defendant Silvio Berlusconi. The analysis intends to investigate, using the methodology of Critical Discourse Analysis (CDA), the press frames referring to a female judge conveyed in newspapers of different political affiliation. The study builds on other research on the media coverage of judicial investigations in Italy, that have demonstrated the existence of a strong political instrumentalization of judicial events (Mancini 2018; Mazzoni et al., 2017) and politicization and instrumentalization of the media representation of the professional category of magistrates (Priulla, 2014). This study will highlight how the professionalism and competence of Boccassini were poorly represented in the Italian press, while a prevalent use of gender stereotypes and an instrumental attention to the judge’s private life can be detected.